Procalcitonin: the ideal predictor of anastomotic leakage. But, when? - Çaparlar, Mehmet Ali; Uçar, Yasin; Dokcu, Şeref; Hasırcı, İsmail; Ulutaş, Mehmet Eşref; Erşen, Ogün (International Surgery Journal, 2021)
Background: Rectal cancer ranks 3rd among the most common malignancies in both sexes. Abdominal infections that can be seen after rectal cancer surgery are the most feared postoperative complications, as they can also be the harbinger of anastomotic leakage. According to its localization, the rate of anastomotic leak varies between 4% and 29.5%. Procalcitonin (PCT) is an increasing parameter in bacterial infections and sepsis. Therefore, it is used to monitor the infection and the effectiveness of the treatment. Our study we aimed to evaluate the effect of PCT on early diagnosis of anastomotic leakage in rectal surgery and the correlation between PCT and CRP and WBC levels. Methods: File records of 50 patients who were operated on for rectal cancer and had anastomosis between 2016 and 2019 were retrospectively analyzed. Demographic features, operation information, preoperative and postoperative clinical features of the patients were recorded. The WBC, CRP and procalcitonin values of the patients were measured on the preoperative and postoperative 1st and 5th days. Patients were divided into two groups as PC values<2 ng/ml and ≥2 ng/ml. Patients with surgical site infections were found. The relationship between hospital stay and PCT levels and those with surgical incision site infection and those with intra-abdominal infection was examined. The correlation between PCT values and CRP and WBC values of the patients was evaluated. Results: There was no significant difference in PCT values in infections at the surgical incision site. However, it was observed that the PCT values of patients with surgical infection in the abdomen were significantly higher than those without (p=0.005). It was observed that the PCT level was high and the duration of hospital stay was observed to be prolonged in patients with infections in the surgical incision area and in the abdomen. Conclusions: PCT can be used as a biochemical parameter in terms of abdominal infection and anastomotic leaks. It is recommended to be checked especially on the fifth postoperative day and to investigate for anastomotic leakage if it is seen to reach the highest value.